Estudo sobre os conhecimentos dos professores de matemática na construção do processo de generalização - Américo, Luciane Ramos (2016)
When researching the construction of the process of generalization of patterns and regularities, many authors were found that consider this study essential to the development of mathematical learning because they present situations of exploration, experimentation and investigation as a way to stimulate the development of thought and algebraic language. Such recognition denotes the important role of teachers through investigation, observation and experimentation during class. In this way, this research seeks to investigate the knowledge that mathematics teachers present about the study of generalizations of patterns and regularities. It is a qualitative research, based on recorded interviews in audio and protocols of resolution of Activities, that allowed us to analyze what pedagogical knowledge and on the teaching of mathematics, the professors of the São Paulo state public network, manifest when solving Activities on standards and regularities, contained in the curricular material used in these schools. For each interviewee we perform an investigation process describing sections of the resolutions, then, based on the theoretical references of this research, we categorize the knowledge presented in knowledge of the mathematical content and pedagogical knowledge. The results obtained after the analysis of the five interviewees allowed us to observe that teachers do not present difficulties in solving activities, but we perceive weaknesses in the knowledge about the importance and possibilities that these activities can offer in the construction of mathematical knowledge. This reflection corroborated with the analysis of the pedagogical knowledge that we consider about the knowledge of the content and the teaching of Algebra. These analyzes allowed us to reflect on how the teachers participating in this research understand the curricular materials available, the comprehension they have about the path chosen by the idealizers of this curriculum for the construction of mathematical knowledge and what possibilities of connections with mathematical concepts could be given in each Learning Situation. During the interviews we could see the interest shown by the teachers in seizing the moment and talking about their apprehensions about the Activities and about what they observe of the learning of their students, as well as the preoccupation with the use of manipulable materials and the mother language To better approximate the knowledge that the student brings as learning and the objective that one wishes to achieve with the proposed activities. The results confirm the fragility that the teachers present in these areas of knowledge and the desire for continuous training that allow the expansion of teaching knowledge